Changing Deliberative Norms on News Organizations' Facebook Sites. Issue 2 (15th October 2014) - Stroud, Natalie Jomini; Scacco, Joshua M.; Muddiman, Ashley; Curry, Alexander L.
Abstract: Comments posted to news sites do not always live up to the ideals of deliberative theorists. Drawing from theories about deliberation and group norms, this study investigates whether news organizations can affect comment section norms by engaging directly with commenters. We conducted a field study with a local television station in a top-50 Designated Market Area. For 70 political posts made on different days, we randomized whether an unidentified staff member from the station, a recognizable political reporter, or no one engaged with commenters. We assessed if these changes affected whether the comments ( n = 2, 403) were civil, were relevant, contained genuine questions, and provided evidence. The findings indicate that a news organization can affect the deliberative behavior of commenters.